2003
DOI: 10.1093/brain/awg072
|View full text |Cite
|
Sign up to set email alerts
|

Preserved myelin integrity and reduced axonopathy in connexin32-deficient mice lacking the recombination activating gene-1

Abstract: Mice heterozygously deficient for myelin protein zero (P0) mimicking human Charcot-Marie-Tooth (CMT) disease 1B show T-lymphocyte and macrophage upregulation in peripheral nerves, which aggravates and modulates the genetically mediated demyelinating neuropathy. In connexin32 (cx32)-deficient (cx32(def)) mice, which mimic the X-linked dominant form of CMT (CMTX), T-lymphocyte and macrophage numbers are also significantly elevated in peripheral nerves. To test the hypothesis that immune cells are indeed pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 41 publications
8
59
0
1
Order By: Relevance
“…Using a rat Mpz promoter, we were able to show that mouse myelinating Schwann cells express human Cx32, that human Cx32 is properly localized to incisures and paranodes, and that human Cx32 "rescues" the demyelinating phenotype in cx32 Ϫ/Y Schwann cells. That the selective expression of human Cx32 in myelinating Schwann cells is sufficient to rescue the phenotype of cx32 Ϫ/Y mice indicates that demyelination initiates the complex events of neuropathy, which includes immune-mediated damage and axonal loss (Kobsar et al, 2002(Kobsar et al, , 2003. Cell autonomy and the pathogenesis of demyelinating neuropathies Dominant mutations in PMP22, MPZ, EGR2, LITAF/SIMPLE, and GJB1, as well as recessive mutations in GDAP1, MTMR2, MTMR13, KIAA1985, NDRG1, PRX, and EGR2 cause demyelinating neuropathies http://www.molgen.ua.ac.be/CMTMutations/DataSource/MutByGene.cfm).…”
Section: Discussionmentioning
confidence: 99%
“…Using a rat Mpz promoter, we were able to show that mouse myelinating Schwann cells express human Cx32, that human Cx32 is properly localized to incisures and paranodes, and that human Cx32 "rescues" the demyelinating phenotype in cx32 Ϫ/Y Schwann cells. That the selective expression of human Cx32 in myelinating Schwann cells is sufficient to rescue the phenotype of cx32 Ϫ/Y mice indicates that demyelination initiates the complex events of neuropathy, which includes immune-mediated damage and axonal loss (Kobsar et al, 2002(Kobsar et al, , 2003. Cell autonomy and the pathogenesis of demyelinating neuropathies Dominant mutations in PMP22, MPZ, EGR2, LITAF/SIMPLE, and GJB1, as well as recessive mutations in GDAP1, MTMR2, MTMR13, KIAA1985, NDRG1, PRX, and EGR2 cause demyelinating neuropathies http://www.molgen.ua.ac.be/CMTMutations/DataSource/MutByGene.cfm).…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages were identified in semithin sections at 400× magnification as cells laden with myelin debris, devoid of a basement membrane, and extending small, microvilli-like processes, as described previously (16,46). The macrophage count was calculated as the ratio per 1,000 myelinated fibers, to account for size differences between different roots and nerves.…”
Section: Methodsmentioning
confidence: 99%
“…To further examine the effect of treatment on inflammation, a well-characterized feature of Cx32 KO mice (16,17), we also immunostained cryosections of lumbar roots and sciatic nerves from 8-mo-old mock-treated (n = 4) and fully treated (n = 4) mice with inflammatory cell markers. This analysis revealed lower numbers of CD68 + macrophages, CD3 + T lymphocytes, and CD45 + leukocytes in anterior spinal roots (Fig.…”
Section: Improved Pathology In Spinal Roots and Peripheral Nerves Ofmentioning
confidence: 99%
“…Finally, a number of studies support the role of secondary immune mechanisms in the pathological changes observed in CMT1X mouse models (Kobsar et al, 2003;Groh et al, 2010). This appears to be a more general phenomenon shared by other inherited demyelinating neuropathies (Ip et al, 2006).…”
Section: Future Challenges and Perspectives In Cmt1xmentioning
confidence: 89%